Pengaruh partisipasi anggaran, kejelasan tujuan anggaran terhadap kinerja aparat pemerintah daerah : komitmen organisasi, budaya organisasi dan locus of control sebagai variabel moderating (Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Shelly Jelita Akhmad; Emrinaldi Nur Dp; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Performance is achievement implementation representation of an action/program/policy in order to achieved objectives, goals, mission and vision of the organization. In order to achieved these objectives it is necessary to pay attention to participation in budgetary participation and clarity of budget goals also commitment organizational, organizational culture and locus of control in relation to decisions related to the budget. This study aims to examine the effect of budgetary participation and clarity of budget goals toward performance of regional government officials in Pekanbaru by examining organizational commitment, organizational culture, and locus of control with serves as moderating variables.The population in this sudy were 26 SKPDs in Pekanbaru. The sample in this study was one person as head of programming/planning department and two persons as of programming/planning department’s staff by the number of respondents 78 peoples from 26 SKPDs. Data collection method using a questionnaire. Data were analyzed using analysis methods SPSS version 17 with multiple linear regression analysis. The results of this research showed : 1) budgetary participation and clarity of budget goals has a significant positive effect on the performance of regional government officials, 2) organizational commitment can not strengthen the relation between budgetary participation and clarity of budget goals toward performance of regional government officials, 3) organizational culture can strengthen the relation between budgetary participation and clarity of budget goals toward performance of regional government officials, 4) locus of control can strengthen the relation between budgetary participation and clarity of budget goals toward performance of regional government officials.Keywords: Budget participation, Clarity of budget goals, Commitment organizational, Organizational culture, Locus of control, local government officials in Pekanbaru city government.